Keberadaan Organisasi Wanita Hindu Dharma Indonesia (WHDI) bagi Eksistensi Budaya Bali di Kota Cimahi - Arini Putri Wiriantiningrum; Dadan Wildan; Siti Komariah; Mirna Nur Alia Abdullah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Maintaining a culture s existence is not easy, the existence of a culture-based organization becomes essential for its existence. This makes the Wanita Hindu Dharma Indonesia (WHDI) Organization have a role in maintaining the existence of Balinese culture. The aim of this research is to find out how the background, contribution, and impact of the WHDI organization on the existence of Bali culture. The research uses a qualitative approach with observational data collection techniques, interviews, documentation studies, and literature studies. The results of this study show that the existence of the Wanita Indonesian Hindu Dharma organization has an impact on the Bali culture s existence through programs run from the respective fields ranging from social, cultural, religious, economic, and organizational.